‘We’re not told why – we’re just told’: qualitative reflections about the Western Australian Go for 2&5 fruit and vegetable campaign - Carter, Owen; Pollard, Christina; Atkins, J.; Milliner, J.; Pratt, Steve (Cambridge University Press, 2011)
Objective: To explore why there is a lack of acceptance among Western Australian (WA) adults of the Go for 2&5®fruit and vegetable social marketing message to consume at least five servings of vegetables per day. Design: A series of focus group discussions comprised of homogeneous groups varied by sex and age, until saturation of themes was achieved, followed by thematic analysis. Setting Part of qualitative research for the Go for 2&5® fruit and vegetable social marketing campaign in WA (2009 population: 2.2 million). Subjects WA adults stratified by sex and age groups (18–29 and 30–55 years) drawn from the second and third quartiles of socio-economic disadvantage. Results: Familiarity with the Go for 2&5® message was excellent. Understanding of what constitutes ‘two servings of fruit’ was excellent and regarded by participants as highly achievable. Understanding of what constitutes ‘five servings of vegetables’ was suboptimal with widespread overestimation contributing to the belief that it is unrealistic. Participants did not know how the 2&5 recommendation was formulated and believed that daily consumption of two servings of fruit and five of vegetables would confer no greater health benefit than one of fruit and three of vegetables. Participants assumed that the 2&5 recommendation was ‘aspirational’ in the sense that it was purposely exaggerated to simply encourage greater overall consumption. Conclusions: A convincing case needs to be presented to WA adults as to why they should consume five servings of vegetables per day. Continuing efforts to educate incorporating what constitutes a serving will assist perceptions that the recommendation is realistic.